Unser Thüringen - Marten, Walter; Boas, Jasper G.; Fischer, Heinz; Koepp, Volker; Raue, Dieter (Icestorm, 2020)
Auf dieser DVD finden Sie Original-Dokumentationen der DEFA von 1955 bis 1986 über Thüringen. [Cover]
Keywords: DVD-Video